Total phosphorus and phosphorus forms change in sediments along the Tone River - Kozyrev, Roman; Umezawa, Yu; Yoh, Muneoki (Frontiers in Earth Science, 2023)
Phosphorus (P), which plays an important role in the metabolism, growth, and development of living organisms, is often the limiting element for primary production in freshwater ecosystems. During flood events, considerable amounts of particulate organic P (org-P) and inorganic P deposited in the basin can be transported by rivers to the ocean. It is important to consider the P distribution from upstream to downstream areas of rivers to understand its transport mechanisms and changes along the course of the river, and thus its flux to the ocean. However, the processes involved in P transformation and cycling among different forms in rivers are poorly understood. To better understand P transformation and total P (TP) concentrations in river basins, P forms such as org-P, Ca-bound phosphorus (apatite, Ca-P), P bound with iron oxides/hydroxides (Fe-P), bio unavailable non-apatite inorganic P (NAIP), and TP were examined in bottom sediments, river bank sediments, parent rock material, and soil samples along the Tone River, Japan. The results indicated an increase in TP concentration in bottom and bank sediment samples along the course of the Tone River. This change in TP was mostly due to the increases in Fe-P and bioavailable org-P, while Ca-P and NAIP decreased toward the downstream area. Analysis of parent rock in three main mountain group areas (Mount Tanigawa, Mount Akagi, and Mount Tsukuba) showed their downstream impacts on TP and the distribution of P forms. Sediment grain size distribution analysis suggested that Fe-P and org-P fractions increased with decreasing sediment particle size, while Ca-P and NAIP were relatively evenly distributed among all grain sizes. Taken together, the data revealed the transformation of P forms in sediments of the largest river in the Kanto region, Japan, which influence its flux to the Pacific Ocean.